A case of severe leptospirosis complicated with massive rhabdomyolysis and acute kidney injury: a case report - Milad Badri; Negar Sheikhdavoodi; Farhad Nikkhahi; Aida Vafae Eslahi; Panagiotis Karanis (Journal of Medical Case Reports)
Abstract Background Leptospirosis is a reemerging waterborne zoonotic infection with a significant global health importance. The manifestations are ranged from mild febrile illness to severe conditions, including Weil’s disease and rhabdomyolysis-induced acute kidney injury. Case presentation Here we report a case of a 27-year-old Iranian male patient with a history of mountain climbing who developed severe leptospirosis. The patient presented massive rhabdomyolysis, acute kidney injury, and respiratory distress, initially suspected to be related to his physical activity. The leptospirosis infection was confirmed using an enzyme-linked immunosorbent assay. Despite hydration and broad-spectrum antibiotic therapy, the patient’s condition demanded intensive care and hemodialysis. Finally, the patient recovered completely, underscoring the critical need for timely diagnosis and intervention in leptospirosis cases. To date, there have been no reports of leptospirosis-associated rhabdomyolysis in Iran. Additionally, cases of rhabdomyolysis caused by leptospirosis are rare worldwide. Conclusion This is report reveals the reemergence of leptospirosis, particularly in environments conducive to the survival of Leptospira bacteria, and the significance of awareness and preventive measures, especially for susceptible populations.